Study of flow, bioheat transfer and cardiac thermal pulse of aneurysm in the abdominal aortic - Ng, Eddie Yin Kwee (2023)
Abdominal aortic aneurysms (AAA) are serious and difficult to detect conditions that can be deadly if they rupture. Infrared thermography (IRT) is a promising imaging technique that can detect abdominal aortic aneurysms more quickly and less costly than other imaging techniques. A clinical biomarker of circular thermal elevation on the midriff skin surface of AAA patient at various scenarios was expected during diagnosis using IRT scanner. However, it is important to note that thermography is not a perfect technology, and it does have some limitations, such as lack of clinical trials. There is still work to be done to improve this imaging technique and make it a more viable and accurate method in detecting abdominal aortic aneurysms. Nevertheless, thermography is currently one of the most convenient technologies in imaging, and it has the potential to detect abdominal aortic aneurysms earlier than other techniques. Cardiac thermal pulse (CTP), on the other hand, was used to examine the thermal physics of AAA. AAA had a CTP that only responded to systolic phase at regular body temperature. Whereas the AAA wall would establish thermal homeostasis with blood temperature following a quasi-linear relationship as the body experienced fever or stage-2 hypothermia. In contrast, a healthy abdominal aorta displayed a CTP that responded to the full cardiac cycle, including diastolic phase at all simulated scenarios.